Teacher Creativity In Forming Character Education - Muhammad Hifdil Islam; Mohammad Hilmy Baihaqy Yussof (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
The law No.20 of 2003 article 3 states that national education in Indonesia has a functions to develop capabilities and shape the character and civilization of a dignified nation in the context of the intellectual life of the land, aiming at improving the potential of learners to become human beings who believe in and have faith in God Almighty, moral noble, healthy, knowledgeable, capable, creative, independent, and be a democratic, responsible citizen. Character education can be seen from two great perspectives, namely how he can recognize, behave and manage himself, and recognize, behave, and lead others. More explicitly, character education is an essential platform for social control based on self-awareness. Based on the research that I have done there turns out to be a significant relationship between the successful application of character education in schools with the creativity of teachers. That is, the more creative a teacher is in implementing character education in schools, the higher the success of character education for students. Based on that conclusion, the authors suggest that every teacher has high creativity in the application of character education in schools. The trick is always to deepen the notion of creativity, the characteristics of creative teachers, and ways to develop creativity. Thus it is expected that the application of character education in schools runs effectively and efficiently.